Central role of carotid body chemoreceptors in disordered breathing and cardiorenal dysfunction in chronic heart failure - Marcus, Noah J.; Del Rio, Rodrigo; Schultz, Harold D. (Frontiers in Physiology, 2014)
Oscillatory breathing patterns are observed in pre-term infants, patients with cardio-renal impairment, and in otherwise healthy humans exposed to high altitude. Enhanced carotid body chemoreflex sensitivity is common to all of these populations and is thought to contribute to these abnormal patterns by destabilizing the respiratory control system. Oscillatory breathing patterns in chronic heart failure (CHF) patients are associated with greater levels of tonic and chemoreflex-evoked sympathetic nerve activity (SNA), which is associated with greater morbidity and poor prognosis. Enhanced chemoreflex drive may contribute to tonic elevations in SNA by strengthening the relationship between respiratory and sympathetic neural outflow. Elimination of carotid body afferents in experimental models of CHF has been shown to reduce oscillatory breathing, respiratory-sympathetic coupling, and renal SNA, and to improve autonomic balance in the heart. The carotid body chemoreceptors may play an important role in progression of CHF by contributing to respiratory instability and oscillatory breathing, which in turn further exacerbates tonic and chemoreflex-evoked increases in SNA to the heart and kidney.